Informal institutions and their comparative influences on social and commercial entrepreneurship: the role of in-group collectivism and interpersonal trust - Pathak, Saurav; Muralidharan, Etayankara (My University, 2016)
We use insights from institutional theory to study how societal collectivism and societal trust facilitate or constrain the emergence of social entrepreneurship (SE) and commercial entrepreneurship (CE). Using 58,918 individual-level responses obtained from the Global Entrepreneurship Monitor (GEM) survey of 27 countries and supplementing with country-level data obtained from the World Values Survey (WVS) and the Global Leadership and Organizational Behavior Effectiveness (GLOBE) study, our results from multilevel analyses demonstrate that while societal collectivism decreases the likelihood of CE, it increases that of SE. Further, while societal trust influences both SE and CE positively, the strength of this positive influence is felt more strongly on SE than CE.
Keywords: social entrepreneurship; informal sector (economics); organizational behavior; organizational effectiveness